Oxaliplatin Depolarizes the IB4– Dorsal Root Ganglion Neurons to Drive the Development of Neuropathic Pain Through TRPM8 in Mice - Wu, Bin; Su, Xiaolin; Zhang, Wentong; Zhang, Yi-Hong; Feng, Xinghua; Ji, Yong-Hua; Tan, Zhi-Yong (Frontiers in Molecular Neuroscience, 2021)
Use of chemotherapy drug oxaliplatin is associated with painful peripheral neuropathy that is exacerbated by cold. Remodeling of ion channels including TRP channels in dorsal root ganglion (DRG) neurons contribute to the sensory hypersensitivity following oxaliplatin treatment in animal models. However, it has not been studied if TRP channels and membrane depolarization of DRG neurons serve as the initial ionic/membrane drives (such as within an hour) that contribute to the development of oxaliplatin-induced neuropathic pain. In the current study, we studied in mice (1) in vitro acute effects of oxaliplatin on the membrane excitability of IB4+ and IB4– subpopulations of DRG neurons using a perforated patch clamping, (2) the preventative effects of a membrane-hyperpolarizing drug retigabine on oxaliplatin-induced sensory hypersensitivity, and (3) the preventative effects of TRP channel antagonists on the oxaliplatin-induced membrane hyperexcitability and sensory hypersensitivity. We found (1) IB4+ and IB4– subpopulations of small DRG neurons displayed previously undiscovered, substantially different membrane excitability, (2) oxaliplatin selectively depolarized IB4– DRG neurons, (3) pretreatment of retigabine largely prevented oxaliplatin-induced sensory hypersensitivity, (4) antagonists of TRPA1 and TRPM8 channels prevented oxaliplatin-induced membrane depolarization, and (5) the antagonist of TRPM8 largely prevented oxaliplatin-induced sensory hypersensitivity. These results suggest that oxaliplatin depolarizes IB4– neurons through TRPM8 channels to drive the development of neuropathic pain and targeting the initial drives of TRPM8 and/or membrane depolarization may prevent oxaliplatin-induce neuropathic pain.